2007
DOI: 10.1111/j.1751-0813.2007.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellaand on‐farm risk factors in healthy slaughter‐age cattle and sheep in eastern Australia

Abstract: Dairy cattle pose the highest risk of all the slaughter-age animals tested. Some of the identified risk factors can be overcome by improved management practices, especially in relation to hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…A similar Salmonella prevalence in feedlot cattle had been reported before and been attributed to low hygiene in feedlots (Vanselow et al 2007;Khaitsa et al 2007a). Also, previous reports of Salmonella prevalence in range cattle (Ranta et al 2005) and dairy cattle (Sorensen et al 2003;Huston et al 2002) have been comparable to what is reported by this study, and have been consistently lower than in feedlot cattle.…”
Section: Salmonella From Clinical Cases Of Animals and Humanssupporting
confidence: 73%
“…A similar Salmonella prevalence in feedlot cattle had been reported before and been attributed to low hygiene in feedlots (Vanselow et al 2007;Khaitsa et al 2007a). Also, previous reports of Salmonella prevalence in range cattle (Ranta et al 2005) and dairy cattle (Sorensen et al 2003;Huston et al 2002) have been comparable to what is reported by this study, and have been consistently lower than in feedlot cattle.…”
Section: Salmonella From Clinical Cases Of Animals and Humanssupporting
confidence: 73%
“…However, higher or lower prevalences were reported in calf and cow dairy herds in other countries (Fossler et al 2005;Nielsen et al 2011). The variations in both herd-and individuallevel prevalences reported in different countries reflect the effects of a wide range of different management risk factors (Vanselow et al 2007;Alam et al 2009;Jones 2011). Cattle herds with Salmonella infection may represent the main animal source of Salmonella infection in human.…”
Section: Discussion Prevalencementioning
confidence: 78%
“…Several factors associated with the reduction or the enhancing of Salmonella fecal shedding were reported; type of production system (Vanselow et al 2007), poor hygiene (Boqvist and Vågsholm 2005), large herd size, lack of a clean visitors' parking area (Davison et al 2006), infected neighboring herds, contact with wild birds and rodents, presence of Salmonella carriers (Nielsen et al 2007), contaminated feeds (Jones 2011), use of nipple feeders (Svensson and Jensen 2007), and access to surface water (lake, pond, river, or stream) (Fossler et al 2005) increased the risk of fecal Salmonella spp. shedding in dairy farms.…”
Section: Introductionmentioning
confidence: 97%
“…This low incidence in sheep and lambs is consistent with similarly low levels reported overseas. A study of slaughter-age lambs in Australia indicated a prevalence of 0.2% for Salmonella in individual animals (Vanselow et al 2007) and a UK study reported a prevalence of 1.1% for Salmonella spp. in the faeces of sheep at slaughter (Milnes et al 2008).…”
mentioning
confidence: 99%